Postmortem : what survives the John Wayne Gacy murders - O'Neil, Courtney Lund (Citadel Press, Kensington Publishing Corp., 2025)
On a December night in 1978, Courtney Lund O'Neil's mother, teenaged Kim Byers, saw her friend Rob Piest alive for the last time. At the end of his shift at the pharmacy where they both worked, fifteen-year-old Rob went outside to speak to a contractor named John Wayne Gacy about a possible job. That night Rob became Gacy's final victim; his body was later found in the Des Plaines River. Kim's testimony, along with a receipt belonging to her found in Gacy's house, proving that Rob had been there, would be pivotal in convicting the serial killer who assaulted and killed over thirty young men and boys. Though she grew up far from Des Plaines, Courtney has lived in the shadow of that nightmare, keenly aware of its impact on her mother. In search of deeper understanding and closure, Courtney and Kim travel back to Illinois. Postmortem transforms their personal journey into a powerful exploration of the ever-widening ripples generated by Gacy's crimes. From the 1970s to the present day, his shadow extends beyond the victims' families and friends -- it encompasses the Des Plaines neighborhood forever marked by his horrific murders, generations of the victims' families and friends, those who helped arrest and convict him, fandom communities, and many others. Layered and thought-provoking, Postmortem is a complex story of loss and violence, grief and guilt, and the legacy that remains long after a killer is caught.